Relationship of mental health and burnout with empathy among medical students in Thailand: A multicenter cross-sectional study - Pitanupong, Jarurin; Sathaporn, Katti; Ittasakul, Pichai; Karawekpanyawong, Nuntaporn (PLOS ONE, 2023)
Objectives To explore mental health, burnout, and the factors associated with the level of empathy among Thai medical students. Background Empathy is an important component of a satisfactory physician-patient relationship. However, distress, including burnout and lack of personal well-being, are recognized to affect a lower level of empathy. Material and methods A cross-sectional study surveyed sixth-year medical students at three faculties of medicine in Thailand at the end of the 2020 academic year. The questionnaires utilized were: 1) Personal and demographic information questionnaire, 2) Thai Mental Health Indicator-15, 3) The Maslach Burnout Inventory-Thai version, and 4) The Toronto Empathy Questionnaire. All data were analyzed using descriptive statistics, and factors associated with empathy level were analyzed via the Chi-square test or Fisher’s exact test, logistic regression., and linear regression. Results There were 336 respondents with a response rate of 70.3%. The majority were female (61.9%). Most participants reported a below-average level of empathy (61%) with a median score (IQR) of 43 (39–40). Assessment of emotion comprehension in others and altruism had the highest median empathy subgroup scores, whereas behaviors engaging higher-order empathic responses had the lowest median empathy subgroup score. One-third of participants (32.1%) had poor mental health, and two-thirds (62.8%) reported a high level of emotional exhaustion even though most of them perceived having a high level of personal accomplishment (97%). The multivariate analysis indicated that mental health was statistically significantly associated with the level of empathy. The participants with higher levels of depersonalization had statistically lower scores of demonstrating appropriate sensitivity, altruism, and behaviors engaging higher-order empathic responding. Conclusions Most medical students had below-average empathy levels, and two-thirds of them had high emotional exhaustion levels, yet most of them reported having a high level of personal accomplishment and good mental health. There was an association between mental health and the level of empathy. Higher levels of depersonalization related to lower scores of demonstrating sensitivity, altruism, and behaviors responding. Therefore, medical educators should pay close attention to promoting good mental health among medical students.